1986
DOI: 10.1139/v86-199
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine isotope effects in the solvolysis of substituted 1-phenylethyl chlorides

Abstract: Kinetic chlorine isotope effects attending the solvolysis of several ring-substituted 1-phenylethyl chlorides in alcohol-water solvent mixtures are reported. The k35/k37 values are insensitive to the identity of ring substituents and to solvent composition. Results are interpreted in terms of an SN1 heterolytic process incorporating a significant amount of internal return. Theoretical calculations suggest that the incipient chloride ion in the transition state may be strongly hydrogen-bonded. On a mesurt les e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The chlorine leaving group kinetic isotope effects obtained by the IRMS method in two different experiments are given in Table . The agreement between the two isotope effects is similar to that reported by Stein and McLennan, who found that repeated measurements of a chlorine isotope effect differ by ∼0.0004.…”
Section: Results and Conclusionsupporting
confidence: 89%
See 1 more Smart Citation
“…The chlorine leaving group kinetic isotope effects obtained by the IRMS method in two different experiments are given in Table . The agreement between the two isotope effects is similar to that reported by Stein and McLennan, who found that repeated measurements of a chlorine isotope effect differ by ∼0.0004.…”
Section: Results and Conclusionsupporting
confidence: 89%
“…Chlorine kinetic isotope effects are a sensitive tool for distinguishing between alternative mechanisms . Although the magnitude of these isotope effects is small (large chlorine kinetic isotope effects are close to 1%), they can be used to indicate whether a bond to a chlorine atom is broken or weakened in the transition state. , Chlorine has two stable isotopes in a proportion suitable for direct measurement of their isotopic ratio, so determining a chlorine isotope effect is both feasible and attractive. , However, determining chlorine isotope effects is impeded by the tedious procedure required for the conversion of chlorine atoms into the gaseous methyl chloride that is required for determining the 35 Cl/ 37 Cl isotopic ratio by isotope ratio mass spectrometry (IRMS). , This obstacle could be avoided if the isotopic composition of a reactant could be determined by direct analysis. In fact, this can be accomplished by determining the 35 Cl/ 37 Cl isotopic ratio of silver chloride samples by fast atom bombardment-isotope ratio mass spectrometry (FAB-IRMS).…”
mentioning
confidence: 99%
“…A continuing research interest of ours has been the ion-pair mechanism for nucleophilic substitutions, especially bimolecular substitutions at saturated carbon (1,2). As part of the mechanistic evidence, P-deuterium kinetic isotope effects were desired.…”
mentioning
confidence: 99%